1999
DOI: 10.1080/10587259908025427
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Sections of Ternary Mixtures: n-docosane + n-tricosane + n-tetracosane

Abstract: The crystallographic long c parameter of the binary and ternary f l , f12, f l , intermediate solid solutions (n-C22H46 + n-C23H48 + n-CZ4H5,,) is approximately equal to the average c parameter of mixture equivalent orthorhombic pure n-alkanes: this finding shows that the longer n-alkane chain is not straight in unit cell of the mixture, but flexible near the chain end, as earlier observed from spectroscopy analyses by other authors. Four ternary isothermal sections were determined at 305K, 308K, 311 K and 313… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…53 (2) Ternary, Quaternary, and Quinary Systems. Nouar et al 193,258 showed that the same intermediate solid solutions β′ n and β′′ n are also present in ternary molecular alloys of consecutive C n 's (C 22 /C 23 /C 24 , Figure 15). As a function of the composition at room temperature, singlephase domains are adjacent to two-phase or three-phase regions (Figure 15).…”
Section: ) Binary Mixtures Of Consecutive C N 'S (∆N C E 2)mentioning
confidence: 98%
“…53 (2) Ternary, Quaternary, and Quinary Systems. Nouar et al 193,258 showed that the same intermediate solid solutions β′ n and β′′ n are also present in ternary molecular alloys of consecutive C n 's (C 22 /C 23 /C 24 , Figure 15). As a function of the composition at room temperature, singlephase domains are adjacent to two-phase or three-phase regions (Figure 15).…”
Section: ) Binary Mixtures Of Consecutive C N 'S (∆N C E 2)mentioning
confidence: 98%
“…Mixing of n-alkanes generally has a dramatic influence on the polymorphic relationships, in particular, when even (n in Cn is even) alkanes are mixed with odd alkanes. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In previous papers we have reported on the phase behavior of a number of individual binary systems. [16][17][18][19][20] For these systems all mixed phases were characterized as to their crystallographic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The structural analyses carried out by X-ray diffraction at ambient temperature ( T = 294.15 K) 4-8 reveal that all of these commercial and synthetic mixtures form a single solid solution, isostructural to the β‘ ordered intermediate phase of binary and ternary C n alloys. …”
Section: Synthetic and Commercial Multi-c N Mixtures With C N Mole ...mentioning
confidence: 99%
“…(i) The mixtures of groups 1 and 2 with N ≤ 11 form a single solid phase whose orthorhombic structure is isostructural to the β‘ or β‘ ‘ ordered intermediate phase of binary and ternary C n alloys. A single periodicity of the molecular layer stacking along the long crystallographic c axis is observed; it corresponds to the mean chain length of a hypothetical orthorhombic odd-numbered C n with a n̄ c number of carbon atoms equal to the n̄ real mean number of carbon atoms of multi-C n mixtures with an excess value close to one carbon atom 5,6 ( n̄ c ≈ n̄ + 1). Thus, all C n 's combine into a single molecular layer: the longer molecules bend to insert themselves between the stacking planes and associate with shorter molecules to obtain a single solid solution with a dense structure.…”
Section: Synthetic Mixtures With C N Mole Fraction Distributions Of ...mentioning
confidence: 99%
See 1 more Smart Citation